2009
DOI: 10.1063/1.3256235
|View full text |Cite
|
Sign up to set email alerts
|

Composition and concentration anomalies for structure and dynamics of Gaussian-core mixtures

Abstract: We report molecular dynamics simulation results for two-component fluid mixtures of Gaussian-core particles, focusing on how tracer diffusivities and static pair correlations depend on temperature, particle concentration, and composition. At low particle concentrations, these systems behave like simple atomic mixtures. However, for intermediate concentrations, the single-particle dynamics of the two species largely decouple, giving rise to the following anomalous trends. Increasing either the concentration of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
46
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 35 publications
1
46
0
Order By: Relevance
“…Recently, thermodynamic and transport anomalies of the fluid phase in the vicinity of the reentrant peaks are investigated. 10,[12][13][14][15][16] Microscopic and structural properties such as the static structure factor in the fluid phase are also reported and documented. 6,7,9,11 These studies revealed that, as the density increases beyond the reentrant peak but at a fixed temperature, thermodynamic and structural properties of GCM becomes more ideal-gas-like, signaled by the lowering of the peak of the structure factors and the better agreement with simple approximations such as the random phase approximation (RPA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, thermodynamic and transport anomalies of the fluid phase in the vicinity of the reentrant peaks are investigated. 10,[12][13][14][15][16] Microscopic and structural properties such as the static structure factor in the fluid phase are also reported and documented. 6,7,9,11 These studies revealed that, as the density increases beyond the reentrant peak but at a fixed temperature, thermodynamic and structural properties of GCM becomes more ideal-gas-like, signaled by the lowering of the peak of the structure factors and the better agreement with simple approximations such as the random phase approximation (RPA).…”
Section: Introductionmentioning
confidence: 99%
“…GCM was first introduced by Stillinger 4 and has been studied by many groups. [5][6][7][8][9][10][11][12][13][14][15][16] Despite of its simple form of the pair potential, GCM exhibits many typical thermodynamic behaviors of the ultra-soft particles. According to thermodynamic phase diagram obtained by numerical simulations, 4,8 GCM basically behaves such as hard spheres at very low densities and temperatures; the crystalline structure in the solid phase is fcc and the freezing/melting temperatures sharply increase with density.…”
Section: Introductionmentioning
confidence: 99%
“…We show that integral equation theory/MCT combination is indeed capable of capturing anomalous behavior of transport coefficients of both neat GC fluids and binary mixtures observed in molecular dynamics (MD) simulations. [5][6][7][8][9][10][11] Our MCT-based microscopic analysis helps to shed further light on the origin and nature of transport anomalies. In particular, we are able to rationalize why viscosity anomaly persists over much more narrow range of densities and temperatures compared to the diffusion anomaly.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Strong theoretical interest in GC model stems from the fact that this bounded potential is useful for describing interactions between inherently penetrable entities, such as polymer coils. [13,15] As such, both thermodynamic [3,16] and dynamic [5][6][7][8][9][10][11] properties of GC fluids and binary mixtures have been extensively studied. It has been found that their transport coefficients exhibit anomalous behavior strongly reminiscent of waterlike model systems [17][18][19][20][21][22][23][24][25][26], with diffusivity increasing and viscosity decreasing with density over a certain range of thermodynamic conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation